1987
DOI: 10.1111/j.1751-1097.1987.tb04846.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematoporphyrin Derivative Uptake by Atheroma in Atherosclerotic Rabbits: The Spectra of Fluorescence From Hematoporphyrin Derivative Demonstrated by an Excimer Dye Laser

Abstract: A new diagnostic and therapeutic endoscopic system consisting of an excimer pulse dye laser is presented. This report demonstrates the accumulation of hematoporphyrin derivative (HpD) in atheroma as shown by the fluorescence of HpD using this equipment. Atheroma was induced in the aorta of WHHL (Watanabe heritable hyperlipidemic) rabbits, 5 mg kg−1 HpD was injected intravenously and the rabbits were sacrificed 24 h later. The aorta was dissected and the localization of HpD was examined. Characteristic peaks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1989
1989
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Such an emission band is also presented by porphyrin solutions in some detergents at premicellar concentrations and may reflect a particular organization of porphyrin molecules at lipid water interface (Miyoshi et al, 1984). We therefore do not agree with the suggestion that an extra emission band in the range 650-670 nm could be characteristic of atheroma as suggested by Okunaka et al, (1987) and Kessel (Kessel and Berguer, 1988). Studies on the accumulation of porphyrins by human atheromatous plaques from aorta obtained at autopsy have been reported by Kessel and Sykes (1984).…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Such an emission band is also presented by porphyrin solutions in some detergents at premicellar concentrations and may reflect a particular organization of porphyrin molecules at lipid water interface (Miyoshi et al, 1984). We therefore do not agree with the suggestion that an extra emission band in the range 650-670 nm could be characteristic of atheroma as suggested by Okunaka et al, (1987) and Kessel (Kessel and Berguer, 1988). Studies on the accumulation of porphyrins by human atheromatous plaques from aorta obtained at autopsy have been reported by Kessel and Sykes (1984).…”
Section: Discussioncontrasting
confidence: 96%
“…In vivo and in vitro emission fluorescence measurements on atheromatous aorta in atherosclerotic rabbits also showed signals similar to those recorded on tumors (Okunaka et al, 1987). These findings suggested that porphyrin binding in tumors and atheroma may be governed by similar interactions with tissue components and/or by the pharmacodynamical properties of these molecules (Okunaka et al, 1987;Pernes et al, 1988). In contrast, Kessel and Sikes (1984) found that human atheromas preferentially bind hematoporphyrin in vitro.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…19 Spokojny et al 22 have shown that HpD was selectively concentrated in different types of arterial lesions in the rabbit model, whereas the media of these tissues exhibited no fluorescence, indicating a decreased or complete lack of HpD uptake. Also Okunaka et al 20 have described in detail how HpD was concentrated in atheromatous lesions of the rabbit with characteristic peaks of the fluorescence at 630, 665, and 690 nm wavelengths after exposure to an excimer pulse dye laser, which was Although DHE is regularly used in combination with photoactivation by laser energy, the results of this study indicate that the application of DHE without photoactivation is also possible for a selective inhibition of plaque cell proliferation at concentrations that do not affect smooth muscle cells from nonatherosderotic arteries. As we demonstrated recently, the photoactivation of DHElabeled smooth muscle cells in culture multiplied the differential effect of this drug (unpublished observations) and thus implicates a possible photodynamic therapy of vascular stenoses.…”
Section: Effect Of Dhe On Cell Proliferation and Cell Size Distributionmentioning
confidence: 98%